Hydration mechanism of partially amorphized β-tricalcium phosphate - Hurle, Katrin; Neubauer, Jürgen; Götz-Neunhoeffer, Friedlinde (Acta Biomaterialia, 2017)
Calcium phosphate cements (CPCs) are applied as bone cements due to their excellent biocompatibility. In the present study, the quantitative phase content development during hydration of partially amorphized β-tricalcium phosphate (β-TCP) within the first 24 h was investigated by in-situ X-ray diffraction (XRD) combined with the G-factor method, an external standard method. The quantity of amorphous phase (ATCP) in the powders was determined by the G-factor method. The hydration model established for partially amorphized β-TCP indicates that ATCP reacted first, followed by the hydration of a small fraction of crystalline β-TCP starting after some h. Consequently, hydration resulted in biphasic samples composed of calcium deficient hydroxyapatite (CDHA) and crystalline β-TCP. The ratio wt%(CDHA)/wt%(β-TCP) after 24 h hydration was adjustable by the initial ATCP content. The crystallinity of CDHA was nearly independent of the ATCP content. Since the biological degradability of CDHA and β-TCP differ, the degradation performance of the set cements is expected to be adjustable by varying the ATCP content. The present study provided a basic understanding of the hydration mechanism of partially amorphized β-TCP, which is the prerequisite for the development of applicable CPC formulations.<br
Keywords: Amorphization; Bone cement; Crystallite sizes; Tricalcium phosphate; XRD quantification